Analysis of the process of administration of the inventories, in the Logistic Agency of the Military Forces in Colombia, in the period 2016-2018 (2019)
This work has as purpose to find the failures in the processes of administration of the inventories that the Logistic Agency of the Military Forces had in the period 2016 - 2018 for which it is fundamental to see the guidelines that since 2016 are in use for the control of the processes, after understanding the guidelines that propose the state of the function The public function is the sense that the process of audits has been developed throughout that period of time, as some examples in which failures are found ; analyzed point by point these failures are sought understand the difficulties that are taken into account at the time of conducting their mission processes. Throughout the development, the work has become the process of managing internal audits from a policy perspective as it has been realized before being one more of the advice and control has been updated. flaws in the limits of the maximum errors.